2009
DOI: 10.1590/s0034-76122009000600010
|View full text |Cite
|
Sign up to set email alerts
|

O impacto das políticas públicas no desenvolvimento de arranjos produtivos locais: o caso do APL de ovinocaprinocultura em Quixadá, Ceará

Abstract: Este artigo enfoca o papel das políticas públicas para o desenvolvimento de arranjos produtivos locais (APLs) na região Nordeste. Uma das formas de o governo alavancar os APLs é com a criação de políticas que apoiem o desenvolvimento dessas aglomerações de empresas. No Brasil, tais políticas de incentivo aos APLs têm se tornado consistentes e já se pode visualizar os resultados satisfatórios de sua implementação. Por meio de um estudo de caso, este artigo analisa o exemplo de um conjunto de políticas implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 3 publications
(1 reference statement)
0
6
0
5
Order By: Relevance
“…The study by Albino, Lima, Souza et al (2010) addresses the influence of public policy on the development of LPAs and offers insights on potentialities and limitations to policymakers. Barroso and Soares (2009) analyzed a set of policies implemented in an LPA in the area of sheep farming, based on the understanding of LPAs as a strategy for local development.…”
Section: Studies On Public Policies For Local Productive Arrangementsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study by Albino, Lima, Souza et al (2010) addresses the influence of public policy on the development of LPAs and offers insights on potentialities and limitations to policymakers. Barroso and Soares (2009) analyzed a set of policies implemented in an LPA in the area of sheep farming, based on the understanding of LPAs as a strategy for local development.…”
Section: Studies On Public Policies For Local Productive Arrangementsmentioning
confidence: 99%
“…Their study differs from that of Barroso and Soares (2009), as the LPAs of the states of São Paulo and Minas Gerais were analyzed based on data related to employment growth, the total value of exports, and the probability of exporting, through the model of fixed effects with weighted methods. Based on their understanding of the LPA development policy, SME performance, and spillovers, the authors concluded that the LPA policy had a direct positive impact on employment and exports.…”
Section: Studies On Public Policies For Local Productive Arrangementsmentioning
confidence: 99%
See 2 more Smart Citations
“…A taxonomia clássica que organizou os tipos de clusters de acordo com a intensidade de suas características foi definida por Mytelka e Farinelli (2000) em três tipos: cluster informal, cluster organizado e cluster inovativo. Estas tipologias possuem o objetivo de compreender a dinâmica de evolução dos APL em Sistemas Produtivos e Inovativos Locais (BARROSO;SOARES, 2009).…”
Section: Tipologiaunclassified